2013
DOI: 10.4236/ajps.2013.412a1007
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Barley Varieties to Aluminum Ions: Separately Effects and Combine with Iron Ions

Abstract: Differences in the barley varieties have been revealed from tolerance to iron (Fe) and aluminum (Al) ions as well as to their combined effect. Received results allowed to separate barley variety into some (three) groups: the first-Al-tolerant varieties, the second-Al-sensitive ones and third-moderately resistant variety. The increased concentration of Fe had practically no effect on biometric (seed germination energy) and cytogenetics (frequency of chromosome aberrations and mitotic index) parameters as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, in natural conditions elevated concentrations of metals with negative impact on cenosis components are generally lower than those selected for an experiment. Polyelemental impact is considered even to a lesser extent, as in this case forecasting of risks is much more difficult, because of possible mutual interactions of metals and synergism or antagonism processes [10]. The studies of barley and wheat sprouts [11] have demonstrated decrease in phytotoxic effect of Al 3+ ions in the presence of Fe 3+ ions, which may be explained by induced synthesis of proteins similar to transferrin or lactoferrin in animals, organic acids or phytochelatins, inactivating Al 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, in natural conditions elevated concentrations of metals with negative impact on cenosis components are generally lower than those selected for an experiment. Polyelemental impact is considered even to a lesser extent, as in this case forecasting of risks is much more difficult, because of possible mutual interactions of metals and synergism or antagonism processes [10]. The studies of barley and wheat sprouts [11] have demonstrated decrease in phytotoxic effect of Al 3+ ions in the presence of Fe 3+ ions, which may be explained by induced synthesis of proteins similar to transferrin or lactoferrin in animals, organic acids or phytochelatins, inactivating Al 3+ ions.…”
Section: Introductionmentioning
confidence: 99%